HUBUNGAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG MALARIA DENGAN PEMILIHAN TERAPI DAUN SUBANG-SUBANG DI KEPULAUAN ENGGANO - Fathnur Sani K; Agung Giri Samudra; Nurwani Purnama Aji (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2020)
the population of Indonesian in 20 provinces in Indonesian was infectes with malaria. In the Enggano Islands, malaria outbreaks are still a fairly large disease in community. This research was conducted in three villages in Enggano namely: Malakoni, Meok and Apoho Village. Respondents were randomly taken, amounting to 40 families, where the data taken is primary data that is data taken directly from community through questionnaires and interviews. The data uses bivariate analysis which is Chi Square. The results of the research that have been carried out can be concluded that there is a significant relationship (p<0,05) between the level of knowledge of malaria and the use of eardrops as an antimalarial drug. The better community’s knowledge, the more people will understand about malaria and the choice of therapy to choose from. The results also showed that 25% of the people in the Enggano Island used subang-subang leaf (Scaevola taccada) therapy treat malaria.